Playing the Game, or Not: Reframing Understandings of Children’s Digital Play - Magladry Madison; Willson Michele (Cultural Science)
Everybody seems to have an opinion about the value, risks and opportunities of children playing digital games. Popular media conveys messages to parents and the public alike of addicted, violent, desensitised, and anti-social children and of the privacy risk of back end data collection. Educationalists waver between seeing digital games as hindering more positive educational, social and physical activity, or as being a new way to engage students and improve learning outcomes. Parents are in fear of the ‘dangers’ of gaming and screen time yet enticed by the educational promise and the entertainment value of keeping their children occupied. Game developers see opportunities for data collection, surveillance and for nudging children’s behaviour and purchases. Many of these fears, hopes, and hype are replaying older tropes that circulate around any new technology, media forms and associated changes in practices, but are amplified further by having children as their central focus. Indeed, all of these stakeholders in children’s futures have particular understandings of what is good for children and what an ideal child should be. Yet children are not docile bodies who simply have things happen to them: they subvert, appropriate and innovate. This paper is a call for an exploration of what and how children’s digital gaming looks like from a child’s perspective and for a reframing of understanding children’s digital play as a result.